5/(x+4)-6x/(3x+12)+7/(2x+8)

Simple and best practice solution for 5/(x+4)-6x/(3x+12)+7/(2x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/(x+4)-6x/(3x+12)+7/(2x+8) equation:


D( x )

x+4 = 0

2*x+8 = 0

3*x+12 = 0

x+4 = 0

x+4 = 0

x+4 = 0 // - 4

x = -4

2*x+8 = 0

2*x+8 = 0

2*x+8 = 0 // - 8

2*x = -8 // : 2

x = -8/2

x = -4

3*x+12 = 0

3*x+12 = 0

3*x+12 = 0 // - 12

3*x = -12 // : 3

x = -12/3

x = -4

x in (-oo:-4) U (-4:+oo)

5/(x+4)-((6*x)/(3*x+12))+7/(2*x+8) = 0

5/(x+4)-6*x*(3*x+12)^-1+7/(2*x+8) = 0

5/(x+4)+(-6*x)/(3*x+12)+7/(2*x+8) = 0

(5*(3*x+12)*(2*x+8))/((x+4)*(3*x+12)*(2*x+8))+(-6*x*(x+4)*(2*x+8))/((x+4)*(3*x+12)*(2*x+8))+(7*(x+4)*(3*x+12))/((x+4)*(3*x+12)*(2*x+8)) = 0

5*(3*x+12)*(2*x+8)-6*x*(x+4)*(2*x+8)+7*(x+4)*(3*x+12) = 0

21*x^2-12*x^3-66*x^2+48*x+168*x+336+480 = 0

216*x-12*x^3-45*x^2+816 = 0

216*x-12*x^3-45*x^2+816 = 0

3*(72*x-4*x^3-15*x^2+272) = 0

72*x-4*x^3-15*x^2+272 = 0

{ 1, -1, 2, -2, 4, -4, 8, -8, 16, -16, 17, -17, 34, -34, 68, -68, 136, -136, 272, -272 }

1

x = 1

72*x-4*x^3-15*x^2+272 = 325

1

-1

x = -1

72*x-4*x^3-15*x^2+272 = 189

-1

2

x = 2

72*x-4*x^3-15*x^2+272 = 324

2

-2

x = -2

72*x-4*x^3-15*x^2+272 = 100

-2

4

x = 4

72*x-4*x^3-15*x^2+272 = 64

4

-4

x = -4

72*x-4*x^3-15*x^2+272 = 0

-4

x+4

x-4*x^2+68

72*x-4*x^3-15*x^2+272

x+4

4*x^3+16*x^2

x^2+72*x+272

-x^2-4*x

68*x+272

-68*x-272

0

x-4*x^2+68 = 0

DELTA = 1^2-(-4*4*68)

DELTA = 1089

DELTA > 0

x = (1089^(1/2)-1)/(-4*2) or x = (-1089^(1/2)-1)/(-4*2)

x = -4 or x = 17/4

x in { -4, 17/4, -4}

3*(x+4)^2*(x-17/4) = 0

(3*(x+4)^2*(x-17/4))/((x+4)*(3*x+12)*(2*x+8)) = 0

(3*(x+4)^2*(x-17/4))/((x+4)*(3*x+12)*(2*x+8)) = 0 // * (x+4)*(3*x+12)*(2*x+8)

3*(x+4)^2*(x-17/4) = 0

( x+4 )

x+4 = 0 // - 4

x = -4

( x-17/4 )

x-17/4 = 0 // + 17/4

x = 17/4

x in { -4}

x = 17/4

See similar equations:

| 1/2m=35 | | .6x=1.5 | | 15x-9=13x-9 | | 8x-4(-7.5)=2 | | 6x-4y= | | 2p+3p-p=9-15-6 | | 180=(x+5)(x+1)x | | 6(0.15+w)=10 | | Z-4.6=-2.2-3z | | 8q-42=-26 | | -54=6z-18 | | 3/2(2x-2)1/5= | | 2(3t-6)=10t-t-6 | | 0.3+2.6=4.4 | | (275)(373-x)(.444)=(100)(x-295)(4.184) | | 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 | | 2x=6-y | | 3.7x-4=2.7x | | (6x-3)(-2x-14)= | | (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 | | c^2=2c+35 | | 9.7/5.9 | | y^2+100=20y | | (x+1)(x-1)(x-8)=0 | | 4z=18-26 | | (6x^3-1x^2+1)/(2x+1) | | (6x-54)/5=-3x | | 30=6r-24+3t |

Equations solver categories